Pregnancy exercise as back pain therapy for pregnant women in the third trimester - Nurhikmah, Nurhikmah; Arsyad, Nur Aliya; Azis, Rezkiawati; Muliyana, Muliyana; Delfiani, Delfiani; Suhartini, Suhartini (Science Midwifery, 2024)
Back pain is a common complaint among pregnant women caused by physiological changes during pregnancy. One effective way to alleviate this discomfort is through prenatal exercise, which includes movements designed to strengthen the abdominal muscles. These muscles play a crucial role in maintaining pelvic stability during physical activities. To evaluate the effectiveness of prenatal exercise in reducing back pain among third-trimester pregnant women. Methods This study employed a quasi-experimental design with a post-test without control approach. Conducted in November 2021 at Campagaloe Health Center, the study involved 41 pregnant women selected through purposive sampling. Data were collected using a pain assessment questionnaire and analyzed with the Wilcoxon Signed Rank Test. Results: Before the intervention, 10 participants (24.4%) reported mild pain, 12 participants (29.3%) reported moderate pain, and 19 participants (46.3%) reported severe pain. After the intervention, 9 participants (22.0%) experienced mild pain, and 32 participants (78.0%) reported moderate pain, while no participants reported severe pain. Statistical analysis revealed a Z-score of -5.282 with a p-value of 0.000 (p < 0.05). Conclusion: Prenatal exercise effectively reduces back pain in third-trimester pregnant women. Midwives are encouraged to provide comprehensive education and training on appropriate prenatal exercise techniques to empower pregnant women to manage pain independently at home.